the proportional equation contains the form
they don't have constant C
like y = mx+ c ( non proportional equation)
so compair the given equation with
y= mx (proportional form)
we have
y= 2x -6 (non proportional)
y= -2x (proportional)
y=0.5x (proportional)
proportional mean y Is changing with change in x but with constant rate.
we remove proportionality
here, k is proportianilty constant.
for example
if we have two-equations.
y = 2x and y = 2x+1
put x= 1 in both equation
y = 2(1) and y = 2(1)+1
y= 2 and y= 3
now put x= 2 in both
y= 2(2) and y = 2(2)+1
y = 4 and y = 5
so you can see that in firs